2019
DOI: 10.19173/irrodl.v20i1.3751
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Participation on Academic Performance in Undergraduate and Postgraduate Students

Abstract: The main objective of this study was to analyse the influence of social media participation on academic performance. The sample consisted of 1960 students taking one of two courses at undergraduate or postgraduate level, respectively (Faculty of Education, National Distance Education University, Spain), of whom 411 students carried out an activity based on social media participation. We used a mixed quantitative (descriptive analysis and ANOVA) and qualitative (content analysis) design. Our results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…So, class participation predicts strongly final grade of the students at the university level. Therefore, class participation is an important variable that should considered to support by faculty members to increase academic achievements of the students The result was consistent with previously reported works (Galyon, Blondin, Yaw, Nalls, & Williams, 2012;Cui, & Coleman, 2020;Pérez-López, & Ibarrondo-Dávila, 2020;Bailey et al, 2020;Santoveña-Casal, 2019;Bek, 2017;Nieuwoudt, 2020;Fematt, et al, 2021;Delfino, 2019;Sezer, Inel, Seçkin, & Uluçinar, 2017;Sothan, 2019;Bielinska-Kwapisz, 2015;Tran, & Pham, 2019), which found out that class participation predicts the final grade. In conclusion hypothesis # 1: The final grade of students described by class participation, is supported.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…So, class participation predicts strongly final grade of the students at the university level. Therefore, class participation is an important variable that should considered to support by faculty members to increase academic achievements of the students The result was consistent with previously reported works (Galyon, Blondin, Yaw, Nalls, & Williams, 2012;Cui, & Coleman, 2020;Pérez-López, & Ibarrondo-Dávila, 2020;Bailey et al, 2020;Santoveña-Casal, 2019;Bek, 2017;Nieuwoudt, 2020;Fematt, et al, 2021;Delfino, 2019;Sezer, Inel, Seçkin, & Uluçinar, 2017;Sothan, 2019;Bielinska-Kwapisz, 2015;Tran, & Pham, 2019), which found out that class participation predicts the final grade. In conclusion hypothesis # 1: The final grade of students described by class participation, is supported.…”
Section: Resultssupporting
confidence: 91%
“…In a blended learning environment, students are too motivated to involve in out-of-classroom activities (Cui & Coleman, 2020); at the same time, Pérez-López & Ibarrondo-Dávila (2020), as well as Xhomara, Stošić & Tomczyk (2019) show that academic progress is directly related, in a positive and significant way to students' priorly interest in the course, the usefulness of the course, prior academic achievement, and applying material learned in practice. Individual backgrounds showed the important role in predicting the academic achievements of undergraduate students (Sothan, 2019;Bailey et al, 2020);and Santoveña-Casal (2019) showed that students who took part in a social media-based activity showed better academic performance than students who did not carry out any learning activity or who took part in a more traditional learning approach. Sikhwari, Dama, Gadisi & Matodzi (2020), indicated that academic as well as social engagement of students at university is important for study commitment, progress, and dropping out preventing; meanwhile, leadership style, feelings of isolation and lack of future aspiration significantly impact teacher-student interaction, and academic performance of students in complex ways (Xhomara, 2018;Bek, 2017).…”
Section: Relationship Between Class Participation and Final Grade Of ...mentioning
confidence: 99%
“…The first selected research from Spain [9]. A sample of 1960 students who were studying one of two courses at the level of undergraduate and postgraduate level respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social networks are considered spaces of social influence, by which actions, thoughts and even feelings are influenced by others connected in the network [ 1 ]. Among different types of influence, there is one called normative social influence, which is defined as the “need to please others” [ 2 ].…”
Section: Introductionmentioning
confidence: 99%